A gallant defense : the Siege of Charleston, 1780 - Borick, Carl P., 1966- (University of South Carolina Press, 2003)
"In 1779, Sir Henry Clinton and more than eight thousand British troops left the waters of New York to try a new tack in the war against the American patriots - capturing the colonies' most important southern port. Clinton and his officers believed that the capture of Charleston, South Carolina, would change both the seat of the war and its character. The British were correct on both counts, but the effect of the charge was defeat. In this comprehensive study of the 1780 siege and surrender of Charleston, Carl P. Borick offers a full examination of the strategic and tactical elements of Clinton's operations."